The biomechanical characteristics of wearing FitFlop™ sandals highlight significant alterations in gait pattern: A comparative study. Issue 4 (May 2015) - James, Darren C.; Farmer, Laura J.; Sayers, Jason B.; Cook, David P.; Mileva, Katya N.
Abstract: Background: The net contribution of all muscles that act about a joint can be represented as an internal joint moment profile. This approach may be advantageous when studying footwear-induced perturbations during walking since the contribution of the smaller deeper muscles that cross the ankle joint cannot be evaluated with surface electromyography. Therefore, the present study aimed to advance the understanding of FitFlop™ footwear interaction by investigating lower extremity joint moment, and kinematic and centre of pressure profiles during gait. Methods: 28 healthy participants performed 5 walking trials in 3 conditions: a FitFlop™ sandal, a conventional sandal and an athletic trainer. Three-dimensional ankle joint, and sagittal plane knee and hip joint moments, as well as corresponding kinematics and centre of pressure trajectories were evaluated. Findings: FitFlop™ differed significantly to both the conventional sandal and athletic trainer in: average anterior position of centre of pressure trajectory ( P < 0.0001) and peak hip extensor moment ( P = 0.001) during early stance; average medial position of centre of pressure trajectory during late stance; peak ankle dorsiflexion and corresponding range of motion; peak plantarflexor moment and total negative work performed at the ankle (all P < 0.0001). Interpretation: The present findings demonstrate that FitFlop™ footwear significantly alters the gait pattern of wearers. An anterior displacement of the centre of pressure trajectory during early stance is the primary response to the destabilising effect of the mid-sole technology, and this leads to reductions in sagittal plane ankle joint range of motion and corresponding kinetics. Future investigations should consider the clinical implications of these findings. Highlights: Gait was investigated in people wearing FitFlop™ footwear. An early change in the centre of pressure location is the primary response. The sagittal plane ankle moment and range of motion are reduced throughout stance. These findings may have clinical relevance.